THE COMPARISON OF RAMANIA (Bouea macrophylla Griff) AND BINJAI (Mangifera caesia) LEAVES EXTRACT GEL EFFECT ON COLLAGEN DENSITY - Nabilah Nabilah; Irham Taufiqurrahman; Nolista Indah Rasyid (Dentino : Jurnal Kedokteran Gigi, 2021)
Background: The extract of ramania Bouea macrophylla Griff) and binjai (Mangifera caesia) leaf have flavonoid compounds that function as antioxidants to balance the amount of Reactive Oxygen Species (ROS) in tissues and optimize wound healing by helping synthesis of hydroxyproline which is used as a collagen synthesis material. Objective: To compare the effect of 15% concentration of ramania leaf extract gel, 15% concentration of binjai leaf extract gel on collagen density in back incision wounds of male Wistar rats on day 7 and day 14. Methods: This study used a true experimental design with a posttest-only with control group design. The study sample used male wistar rats that were healthy and active, aged 2-3 months with a body weight of 250-300 grams. The total sample was 18 rats divided into 6 groups. The 15% concentration of ramania and binjai leaves was given topically, then the rats were euthanized on the 7th and 14th day. Collagen index measurement was using hydroxyproline concentration. Results: Two-way Anova data analysis showed a significant value of 0.00 (p<0.05), which means that there was a difference in effect between the treatment gel and wound day. Bonferroni Post Hoc test showed a significant value in all treatment gel groups. Conclusion: There is a difference in the effect of 15% concentration of ramania leaf extract gel and 15% concentration of binjai extract gel on collagen density. Binjai leaf extract gel at 15% concentration is more effective for collagen density than Ramania leaf extract at 15% concentration and placebo. Keywords : Binjai Leaf Extract Gel, Collagen, Hydroxyproline, Ramania Leaf Extract Gel.